Penerapan Konsep Good Governance dalam Pelayanan Publik di Pemerintahan - Muhammad Islahuddin (Laskar Karya, 2025)
The provision of public services is a fundamental responsibility of the state to meet the basic needs and civil rights of every citizen through accessible goods, services, and administrative functions. However, persistent problems in public administration highlight the need for comprehensive reform to ensure that governance becomes more professional, accountable, and trustworthy. This study aims to analyse current challenges in the provision of public services within the framework of good governance, as well as to provide legal and structural recommendations to improve bureaucratic performance. The study uses a normative legal research method, employing a legal and conceptual approach to analyse legal norms and governance theories relevant to public administration. The findings show that structural weaknesses in the bureaucracy, particularly in the budgeting process for public services, significantly hinder the effective provision of services. In addition, the quality of public services remains suboptimal due to a rigid bureaucratic culture and resistance to innovation and citizen-oriented practices. Another contributing factor is the behaviour of state officials, who often display a mindset of privilege and authority rather than service and responsiveness. These issues reflect a deeper misalignment between the normative idealism of good governance and its implementation in practice. Based on these findings, the study recommends legal and institutional reforms aimed at strengthening budget accountability, promoting a culture of service within the bureaucracy, and raising the ethical standards of public officials to align with the principles of good governance and the rule of law.